CYP2C9*8 is prevalent among African––Americans: implications for pharmacogenetic dosing. (August 2009) - Scott, Stuart A; Jaremko, Malgorzata; Lubitz, Steven A; Kornreich, Ruth; Halperin, Jonathan L; Desnick, Robert J
Aims: Although the frequencies of pharmacogenetic variants differ among racial groups, most pharmacogenetic algorithms for genotype-guided warfarin dosing only include two CYP2C9 alleles ( *2 and *3 ) and a single VKORC1 allele (g.-1639G>A or g.1173C>T) commonly found among Caucasians. Therefore, this study sought to identify other CYP2C9 and VKORC1 alleles important in warfarin dose variability and to determine their frequencies in different racial and ethnic groups.Materials & methods: The CYP2C9 and VKORC1 genes were sequenced in selected sensitive (<21 mg/week) and resistant (>49 mg/week) individuals with discrepant therapeutic and algorithm-predicted warfarin doses based on prior CYP2C9 and VKORC1 genotyping. The CYP2C9 and VKORC1 allele frequencies were determined in healthy, racially self-identified blood donors.Results: Sequencing identified an African––American male with a lower than predicted therapeutic warfarin dose (14.4 mg/week), previously genotyped as CYP2C9*1/*1, who was homozygous for CYP2C9*8 (c.449G>A; p.R150H). Genotyping 600 African––American alleles identified CYP2C9*8 as their most frequent variant CYP2C9 allele (0.047), and the combined allele frequency of CYP2C9*2, *3, *5, *6, *8 and *11 was 0.133. Given most warfarin pharmacogenetic dosing algorithms only include CYP2C9*2 and *3, the inclusion of CYP2C9*8 alone could reclassify the predicted metabolic phenotypes of almost 10% of African––Americans, or when combined with CYP2C9*5, *6 and *11, more than 15%. In addition, the African––American VKORC1 g.-1639A allele frequency was 0.108 and three g.1331G>A (p.V66M) carriers were identified.Conclusions: CYP2C9*8 is prevalent among African––Americans (∼∼1 in 11 individuals). Thus, in this racial group, the incorporation of CYP2C9*8 into genotyping panels may improve dose prediction of CYP2C9-metabolized drugs, including warfarin.